2022
DOI: 10.1021/acsomega.1c06787
|View full text |Cite
|
Sign up to set email alerts
|

Gold and Platinum Nanoparticle-Functionalized TiO2 Nanotubes for Photoelectrochemical Glucose Sensing

Abstract: Developing stable photoelectrochemistry (PEC) glucose biosensors with high sensitivity and a low detection limit is highly desirable in the biosensor field. Herein, a highly sensitive and stable enzymatic glucose PEC biosensor is rationally designed and fabricated using a TiO2NTs/Au/Pt/GOx electrode. First, we prepared one-dimensional TiO2 nanotube arrays which could realize the orthogonalization of the light-incident direction and the carrier diffusion direction via anodization. Subsequently, we used the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Tests were performed at higher concentrations; however, the stability and selectivity will be reduced at low concentrations (<0.8 mM). So, it can be said that gold and platinum nanoparticles have a synergistic effect on glucose-sensing due to their photocatalytic properties [ 66 ].…”
Section: Platinum Nanoparticles Functionalizationmentioning
confidence: 99%
“…Tests were performed at higher concentrations; however, the stability and selectivity will be reduced at low concentrations (<0.8 mM). So, it can be said that gold and platinum nanoparticles have a synergistic effect on glucose-sensing due to their photocatalytic properties [ 66 ].…”
Section: Platinum Nanoparticles Functionalizationmentioning
confidence: 99%
“…Titanium dioxide was one of the first materials chosen for these analyses, considering its known photocatalytic properties [5–11] . However, this material has some disadvantages, due to the rapid recombination of the photogenerated charges and good activity only under intense UV light.…”
Section: Introductionmentioning
confidence: 99%
“…The photogenerated electrons can in fact remain in the nanoparticles, after the transfer through the interface, and the formation of a Schottky barrier turns out to be an efficient electron trap to prevent recombination. Furthermore, if metals with localized surface plasmon resonance (LSPR) properties are used, such as Au and Ag, the absorption in the visible region is also increased [9,16–20] …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been found that noble metal nanoparticles with surface plasmon resonance (SPR) characteristics can improve the optical conversion efficiency of TiO 2 [36]. In particular, gold nanoparticles (AuNPs), because of their good stability, biocompatibility, synthetic controllability, and excellent catalytic performance [37], have become the research hotspot of SPR-enhanced optical activity [38,39].…”
Section: Introductionmentioning
confidence: 99%